Competitive inhibition of iron absorption by manganese and zinc in humans - Rossander-Hultén, L; Brune, M; Sandström, B; Lönnerdal, B; Hallberg, L (The American journal of clinical nutrition, 1991)
Zinc and manganese may interfere with iron absorption because of similar physicochemical properties and shared absorptive pathways. The effects of zinc and manganese on iron absorption were studied in human subjects by using paired observations and a dual-radioisotope method (55Fe and59Fe). Manganese inhibited iron absorption both in solutions and in a hamburger meal. Fractional iron absorption is strongly dose dependent. Adding 2.99 mg Mn to 0.01 mg Fe reduced iron absorption to the same extent as increasing the iron dose 300-fold to 3 mg, strongly indicating a direct competitive inhibition of manganese on iron absorption. In the same experiment with zinc, no inhibitory effect was observed, suggesting different pathways for the absorption of zinc and iron. An intraluminal interaction may occur, because a fivefold excess of zinc to iron (15 mg Zn/3 mg Fe) reduced iron absorption by 56% when given in a water solution but not when given with a hamburger meal.